Canid Coprolites from the Late Pleistocene of Hidalgo, Central Mexico: Importance for the Carnivore Record of North America. Issue 4 (2nd October 2017) - Bravo-Cuevas, Victor M.; Morales-García, Nuria M.; Barrón-Ortiz, Christian R.; Theodor, Jessica M.; Cabral-Perdomo, M. A.
ABSTRACT: We present the first reported occurrence of canid coprolites from the late Pleistocene of central Mexico. The sample consists of five associated coprolites recovered from Quaternary deposits that crop out in southeastern Hidalgo, central Mexico. The material shows several of the typical features of canid feces, including elongated cylindrical shape, uncommon and nondistinct constrictions, and one tapered end. The coprolites are similar in size to feces of North American foxes, such as Vulpes macrotis, V. lagopus, V. vulpes, and Urocyon cinereoargenteus ; likewise, their size might be comparable to those of the Pleistocene canid Canis cedazoensis . The content of the studied coprolites consists of numerous teeth and bone fragments referable to the pocket gophers Pappogeomys or Cratogeomys . The coprolite content is related to a mostly carnivorous diet comparable to that of C. cedazoensis, wolves ( Canis lupus, C. rufus, and C. dirus ), and some foxes ( V. macrotis and V. velox ). As a result, it is proposed that the potential trace maker of the coprolites could be a form similar to a carnivorous fox or a small dog. These trace fossils represent the first indirect evidence of canids in the late Pleistocene of Hidalgo and provide additional information regarding the geographic distribution of the Canidae in temperate areas of North America that now are part of central Mexico during the second half of the Pleistocene.